Surgical frequency analysis of patients clustered according to postoperative pain trajectory: a retrospective study - Qurani Alifitriah Tartar; Kyung Nam Park; Kwang-Suk Seo; Myong-Hwan Karm (Scientific Reports)
Abstract Oropharyngeal and orthognathic surgeries cause more postoperative pain than simple dental procedures. The lack of detailed pain pattern analysis after dental surgeries makes pain management challenging. We assessed postoperative pain patterns in patients undergoing various dental surgeries, categorized based on changing pain levels, and identified the most frequent surgical procedures within each pain pattern cluster. Patients aged 18 years and older undergoing elective oral and maxillofacial surgeries under general anesthesia and hospitalized for > 36 h were included. Exclusion criteria were COPD, head injury, adverse drug reactions, substance misuse, severe metabolic disorders, infections, or psychiatric conditions. We retrospectively analyzed previously collected postoperative visual analog scale (VAS) data at 0, 6, 12, 24, and 36 h postoperatively from 790 patients undergoing various dental surgeries under general anesthesia using k-means clustering to identify pain patterns. Surgery type, duration, and patient-controlled analgesia were analyzed for three pain clusters. Cluster 1 had high prolonged initial pain (VAS 7.43 ± 1.62), mostly involving extensive oropharyngeal cancer surgeries. Cluster 2 experienced moderate pain initially (VAS 5.95 ± 1.44), steadily declining, typically involving orthognathic surgeries. Cluster 3 reported moderate initial pain (VAS 5.21 ± 1.49) that decreased rapidly. Extensive procedures were common in Cluster 1, whereas simpler excisions were prevalent in Cluster 3. Postoperative pain varies significantly according to the extent and invasiveness of surgery. Identifying specific pain trajectories based on detailed surgical assessments can enhance preemptive pain management and aid clinicians in predicting and managing postoperative pain.